Female Emancipation amidst Religious Patriarchy in Tara Westover’s Educated: A Feminist Literary Analysis - Utami, Ananda Fathiyyah; Istiani, Imas (Jurnal Bahasa dan Sastra, 2025)
This study investigates the underexplored representation and contestation of religiously grounded patriarchal systems in contemporary feminist literary studies, focusing on memoirs. It analyzes mechanisms of women’s oppression and forms of female resistance in Tara Westover’s Educated through qualitative narrative analysis of key episodes, including domestic violence, educational mobility, and religious indoctrination. Employing Sylvia Walby’s framework of patriarchal structures alongside Mary Daly’s critique of androcentric theology, the study identifies two central modes of patriarchal control. First, domestic patriarchy is embodied by Tara’s father, Gene, whose religious authority governs family behavior and restricts access to education and external institutions, illustrating how religious doctrine enforces hierarchical gender relations within the household. Second, Tara’s resistance emerges through her pursuit of academic achievement and financial autonomy, marking a gradual disengagement from domestic control and a redefinition of her subjectivity. Her intervention in her sister-in-law’s experience of domestic violence further exemplifies a shift from compliance to active moral agency. The analysis expands Walby’s model by revealing how religious ideology sustains domestic patriarchy even as women engage with broader social institutions. This article contributes to feminist literary criticism by illuminating the complex interplay of religious indoctrination and familial patriarchy in Educated, and by framing education as a situated form of resistance within patriarchal religious contexts.